Fractionation of heavy metals in yellow latosol cultivated with vegetables - Silva, Laercio Santos [UNESP]; Luna Galindo, Izabel Cristina de; Filla, Vinicius Augusto [UNESP]; Gomes, Romario Pimenta [UNESP]; Campos, Milton Cesar Costa; Rabelo de Souza Bahia, Angelica Santos [UNESP]; Cunha, Jose Mauricio da (Univ Estadual Londrina, 2018)
Sequential extraction or chemical fractionation of heavy metals allows inferences to be made about their origin, occurrence, bioavailability, toxic potential and environmental contamination. Thus, the present study aimed to assess the distribution of Cu, Mn, Ni, Pb and Zn among the different soil fractions and landscape compartments of a yellow latosol cultivated with vegetables. Soil samples were collected from five areas cultivated with tomato (Lycopersicon esculentum, Mill.), lettuce (Lactuca sativa), chili pepper (Capsicum annuum L.) and chard (Beta vulgaris L.) in different slope positions (upper, middle, lower), and four reference areas (native forest), at a depth of 0.00 - 0.20 m. Heavy metal levels were also assessed in water used to irrigate the crops and for human consumption by collecting 200 ml of water samples from reservoirs. The soil samples were sequentially fractionated to quantify the concentrations of adsorbed Cu, Mn, Ni, Pb and Zn in the exchangeable (EF), organic matter (OF), amorphous and crystalline iron oxide fractions (AFeOx and CFeOx). Landscape position only interfered significantly in heavy metal adsorption in the soil for Cu and Ni associated with CFeOx and Zn bound to the EF in the farming areas. The highest Cu, Ni, Pb and Zn levels were found in the fractions with less stable chemical bonds (bound to organic matter), in addition to a strong affinity between Cu, Zn and Mn and the oxide fractions (AFeOx + CFeOx). The low affinity of Pb and Ni for the AFeOx and CFeOx fractions indicates greater contamination potential for the water reservoirs. In the short term, organic matter is the main source of remediation for heavy metal contamination in soil, making it important to adopt conservation practices aimed at reducing OM losses.
Keywords: Chemical extraction; Soil contamination; Soil pollution; Environmental monitoring